MEDIA COMMERCIALIZATION: INDOSIAR TELEVISION STATION EFFORT TO INCREASE RATINGS - Husna, Zida Zakiyatul (QAULAN: Journal of Islamic Communication, 2021)
Media is an industry that can produce commodities that make commercial elements more prominent. Commercial itself is an implication of the media revolution that encourages media with an economic vision. The party that determines the communication process, from information coverage, information packaging, to information marketing is the owner of capital, where this condition affects the vision of a media. It can be said that the idealism of the media really depends on the owners of capital, because the form of journalism that is packaged is focused on dealing with market opportunities. Seeing this background, this research focuses on how the efforts of an Indosiar television station in increasing ratings. This study uses a descriptive qualitative method by observing the Indosiar television station. In this study, it was explained that one of the efforts of Indosiar television station in increasing its rating was from the rising artist performance factor.